Implementasi Penyetoran Dan Pelaporan Pajak Penghasilan (Pph) Pasal 23 Dengan Menggunakan Coretax: Studi Kasus Pada PT X - Nanda Wahyu Saputra; Nurul Fitriani (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
Abstract Income Tax (PPh) Article 23 is known as income tax which in the tax year is deducted by the withholding agent on income in the form of dividends, interest, royalties, gifts and awards, rent, compensation for other services as determined by the Director General of Taxes, except for the withholding of Income Tax (PPh) which is final in nature. The process of depositing and reporting this type of PPh often faces various challenges, especially in terms of timeliness and compliance with applicable tax regulations. Digitalization in taxation has encouraged companies to switch to a tax application system in the form of Coretax in order to increase efficiency and accuracy in fulfilling tax obligations. Coretax is one of the applications used in tax management, including in the deposit and reporting of PPh Article 23. Analyzing the implementation of Coretax in the process of depositing and reporting PPh Article 23 at PT X is the purpose of this study. The case study research method with a qualitative approach was used in this study. Data was obtained through observation, interviews, and analysis of relevant documents. The results of this study reveal that the implementation of Coretax brings significant changes to the company's tax administration system, especially by replacing the role of DJP Online through a more standardized and systematic reporting structure. However, the effectiveness of Coretax use in PT X is still not optimal due to various obstacles, such as technical disruptions to the system, lack of socialization from the tax authorities, and the absence of significant improvements in operational efficiency. Therefore, a comprehensive evaluation and improvement of the Coretax system is needed so that it can provide optimal contributions in supporting smooth tax reporting and increasing tax compliance of business actors.) Keywords: Coretax, Article 23 Income Tax, Tax Deposit, Tax Reporting.